THE POTENTIAL AND THE BENEFITS OF USING SOCIAL MEDIA IN THE LIBRARY - Pylypenko, Nataliya Volodymyrivna (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article examines and discusses the need for the active use of social media for communication with the library users and meeting their informational needs. The features of the current stage and prospects of further development of the library Internet-representation in social networks are determined.